Smallholder farming and crop variety choice: Wheat variety choice in Pakistan - Nazli, Hina; Asare-Marfo, Dorene; Smale, Melinda; Malik, Sohail Jehangir; Birol, Ekin (International Food Policy Research Institute, 2014)
Zinc is an important nutrient for human health, especially for the growth of children (Caulfield and Black 2004). In 2011 Pakistan’s National Nutrition Survey found that zinc deficiency is high (47 percent) among children under-five years of age and women of child-bearing age. Nearly 42 percent of non-pregnant women, 48 percent of pregnant women, and 37 percent of children are estimated to be zinc deficient.